South American digital diplomacy: approaches before and after the Russian-Ukrainian crisis - Tasențe, Tănase; Stan, Mari-Isabella (Cuadernos.info, 2024)
In the digital age, diplomacy integrates traditional methods with modern tools such as social media. E-diplomacy enhances global dialogue, but struggles with misinformation and requires strategic communication. This study examined the Twitter reactions of 11 South American presidents to the Russo-Ukrainian war, specifically to Russia's aggression on 24 February 2022. Tweets from February to April 2022 were analysed using Fanpagekarma and RStudio. Engagement metrics and sentiment were assessed across three phases. The results show South America's different diplomatic approaches to the conflict. Venezuela's Maduro supported Russia, in contrast to Western views, while Argentina's Fernández emphasised diverse relations and advocated post-invasion peace. Leaders such as Lasso and da Silva had limited tweets, suggesting neutrality or a local focus. Others, including Ali and Benítez, remained silent. Castillo's tweets focused largely on Ukraine. Chile advocated international law, Brazil leaned towards neutrality, and Peru emphasised its citizens. Maduro criticised Western sanctions and the media. The Ukraine issue highlights South America's nuanced digital diplomacy, reflecting different responses to Russia's actions.